2010
DOI: 10.2478/v10042-008-0089-1
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the E-cadherin-catenin complex in patients with pancreatic ductal adenocarcinoma.

Abstract: Cadherins and catenins, mediators of intercellular interactions, play a major role in adhesion. Changes in their expression and functioning reflect invasive and metastatic properties of cancer cells. The study objective was to assess changes in the expressions of E-cadherin and α-, β-and γ-catenin proteins in pancreatic duct carcinoma in correlation with clinicopathological parameters, lymph node involvement and distant metastases. Twenty-nine patients with pancreatic duct carcinoma were analyzed in relation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
9
1
Order By: Relevance
“…We observed lower E-cadherin expression more frequently in male patients and higher in female patients, but there was no significant difference in survival between men and women. Contrary to our study, Pryczynicz et al did not find a correlation between E-cadherin expression and patient gender [21].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We observed lower E-cadherin expression more frequently in male patients and higher in female patients, but there was no significant difference in survival between men and women. Contrary to our study, Pryczynicz et al did not find a correlation between E-cadherin expression and patient gender [21].…”
Section: Discussioncontrasting
confidence: 99%
“…Pećina-Šlaus et al found lower E-cadherin expression in higher-grade meningeomas [20]. Hong et al [11] also demonstrated that lower expression of E-cadherin was more common in high-grade PDAC, while Pryczynicz et al [21] did not find a correlation between E-cadherin expression and tumor grade or lymph node metastases. An in vitro study using JHP-1 adenocarcinoma cell line showed that the downregulation of E-cadherin in pancreatic carcinoma cells promoted the invasiveness into the basement membrane, and similarly in vivo selection of highly metastatic murine pancreatic cancer cells induced EMT by genetic inactivation of E-cadherin in parental cells [22,23].…”
Section: Discussionmentioning
confidence: 98%
“…Independent of the buffer no E-Cadherin expression could be detected for pancreas carcinoma and the lymph node sample. This is not astonishing as lymphocytes do not express the protein and down-regulation of E-Cadherin in pancreas carcinoma may occur [13], [14].…”
Section: Resultsmentioning
confidence: 98%
“…Absent or reduced ␣-catenin expression increases tumorigenic characteristics in vitro (37) and has been documented in esophageal, lung, stomach, pancreatic, and colorectal cancers (36,38,50). It has also been associated with metastasis (10,11).…”
Section: Discussionmentioning
confidence: 99%